2007
DOI: 10.1111/j.1600-0722.2007.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental fluorosis and dental caries among 12‐yr‐old children from high‐ and low‐fluoride areas in Lithuania

Abstract: We investigated the prevalence and severity of dental fluorosis, and the occurrence of dental caries, among 12-yr-old children from high- and low-fluoride areas in a country with high caries figures and a developing oral healthcare system. The sample included a total of 600 lifetime residents from high-fluoride (HF; 1.7-2.2 ppm) and low-fluoride (LF; 0.2 ppm) areas in Lithuania. The diagnoses of dental fluorosis followed the Thylstrup-Fejerskov Index (TF), and a diagnosis of dental caries followed the World He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 34 publications
3
23
0
3
Order By: Relevance
“…The dose dependent effect of fluoride has been reported in several human and animal data (Dhar & Bhatnagar, 2009). The incidence of dental fluorosis in the high fluoride area is higher than that in the low fluoride area (de Moura et al, 2013;Narbutaite, Vehkalahti, & Milciuviene, 2007). For example, sheep teeth treated with low dose of fluoride for a long time and high dose of fluoride for a short time exhibited different phenotypes.…”
Section: Discussionmentioning
confidence: 96%
“…The dose dependent effect of fluoride has been reported in several human and animal data (Dhar & Bhatnagar, 2009). The incidence of dental fluorosis in the high fluoride area is higher than that in the low fluoride area (de Moura et al, 2013;Narbutaite, Vehkalahti, & Milciuviene, 2007). For example, sheep teeth treated with low dose of fluoride for a long time and high dose of fluoride for a short time exhibited different phenotypes.…”
Section: Discussionmentioning
confidence: 96%
“…However, most studies examining the effects on the damages to children's intellectual ability and other aspects were conducted in regions where residents were exposed to relatively high fluoride levels (more than 3 mg/L) [5,6,13,14] while the majority of residents living in endemic fluorosis areas have been exposed to lower fluoride levels in their daily life. Although some studies [15,16] in which the fluoride exposure levels were relatively low had reported associations between low fluoride exposure and the negative effects among children, the analysis focused specifically on children's dental fluorosis condition rather than intellectual performance.…”
Section: Introductionmentioning
confidence: 99%
“…Paaiškėjo, kad KPI-D indekso vidurkis įvai-riuose regionuose svyruoja, pvz., Šiauliuose jis yra 1,13 (1,43), tačiau Panevėžyje ėduonies intensyvumas išlieka gana didelis -2,91 (2,35) (2 lentelė). Nevienodą dantų ėduonies paplitimą ir intensyvumą lemia skirtingas fluoridų kiekis įvairių Lietuvos regionų geriamajame vandenyje (22,23). Visuotinai pripažįs-tama, kad fluoridų preparatai stabdo dantų ėduonies atsiradimą.…”
Section: Kristina Saldūnaitė Alina Pūrienė Simona Milčiuvienė Ir Ktunclassified
“…Daugiausia silantu dengtų dantų turi Vilniaus miesto moksleiviai (21 689 dantys), mažiausiai -Klaipėdos (tik 8474 dantys). Toks skirtingas dantų dengimo silantu skaičius gali būti nulemtas didelio fluoridų kiekio Klaipėdos geriamajame vandenyje (1,7-2,2 mg/l) (22,23). Dėl įrodyto antikariesogeninio fluoridų poveikio šiame regione gyvenančių vaikų dantų vagelės ir duobelės dažnai jau yra subrendusios, kietos.…”
Section: -12 Metų Lietuvos Moksleivių Krūminių Dantų ėDuonies Profilunclassified